Integration of the HEART and SHERPA Approach to Evaluating Human Errors in the Refinery Salt Production - Rammadaniya, Putri; Mahbubah, Nina (TALENTA Publisher, 2022)
Human error can be prevented by measuring human reliability through the Human Reliability Assessment approach. PT A is a national scale salt producer that produces salt. The quality division identifies human error problems made by operators in the salt refining process. This study aims to identify, calculate probability values, and provide recommendations for improvement to reduce human error in salt refining production operators. HEART and SHERPA are research approaches used because they are considered the most suitable for this study. The results showed that the most visible human error for the error mode category was C2, incomplete checking, and 42 error modes because the operator infrequently did a complete check. The process with the highest Human Error Probability value is the drying process 1, with a value of 7.49. In contrast, the process with the most minor Human Error Probability value score of 0.085 is the bagging process 2. Human error prevention efforts are carried out for each process based on the highest score on the Human Error Probability Index, including Personal Protective Equipment, Standard Operating Procedures, and training to improve operator skills.